2018
DOI: 10.1038/s41467-018-05423-x
|View full text |Cite
|
Sign up to set email alerts
|

Transient marine euxinia at the end of the terminal Cryogenian glaciation

Abstract: Termination of the terminal Cryogenian Marinoan snowball Earth glaciation (~650–635 Ma) is associated with the worldwide deposition of a cap carbonate. Modeling studies suggest that, during and immediately following deglaciation, the ocean may have experienced a rapid rise in pH and physical stratification followed by oceanic overturn. Testing these predictions requires the establishment of a high-resolution sequence of events within sedimentary records. Here we report the conspicuous occurrence of pyrite conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Xinyu CIF was deposited in a deep marine setting based on sedimentary facies analysis (Tang et al, 1987) and palaeogeographic reconstruction (Wang and Li, 2003), therefore the spread of ocean euxinia is recorded by the deep Xinyu CIF, but not in other shallow CIFs as Fe(II) delivery was cut in deeper seawater. A recent study reported widespread euxinia at the end of Marinoan glaciation, whereby the abundance of pyrite nodules was significantly greater in deep settings than in shallow settings (Lang et al, 2018). We therefore argue that the spread of euxinia into deep oceans and titration of hydrothermal Fe 2þ by sulfides is a viable mechanism to explain the disappearance of IFs after the Cryogenian Period.…”
Section: Discussionmentioning
confidence: 71%
“…Xinyu CIF was deposited in a deep marine setting based on sedimentary facies analysis (Tang et al, 1987) and palaeogeographic reconstruction (Wang and Li, 2003), therefore the spread of ocean euxinia is recorded by the deep Xinyu CIF, but not in other shallow CIFs as Fe(II) delivery was cut in deeper seawater. A recent study reported widespread euxinia at the end of Marinoan glaciation, whereby the abundance of pyrite nodules was significantly greater in deep settings than in shallow settings (Lang et al, 2018). We therefore argue that the spread of euxinia into deep oceans and titration of hydrothermal Fe 2þ by sulfides is a viable mechanism to explain the disappearance of IFs after the Cryogenian Period.…”
Section: Discussionmentioning
confidence: 71%
“…3c) and framboidal ( Fig. 4l), suggesting an authigenic origin related to BSR (Lang et al 2018). Secondly, δ 34 S py values range from − 41.20 to − 19.70‰ (unpublished data), all of which are obviously lower than the δ 34 S value (approximately + 10‰) of seawater sulfate in the late Permian (Strauss 1997); thus, fractionation of − 51.20‰ to + 29.70‰ occurred.…”
Section: Implications For the Late Permian Marine Environmentmentioning
confidence: 94%
“…However, unlike the Cenozoic, the low atmospheric oxygen and anoxic deep ocean of the Neoproterozoic allowed evaporite-derived oxidizing power to be effectively transmitted into a negative δ 13 C signal. Such imbalance, potentially driven by weathering events and related positive feedbacks, may be particularly relevant to the ending and immediate aftermath of 'Snowball Earth' glaciations, which are marked by euxinia and anomalously high levels of pyrite deposition (Sahoo et al, 2012;Lang et al, 2018).…”
Section: Environmental Effects Of Sulfur Cycle Imbalancementioning
confidence: 99%